Graduate Tracer Study for Refining TVET Programs - Shrestha, Diwat Kumar (Journal of Technical and Vocational Education and Training, 2021)
The Technical Vocational Education and Training (TVET) is key to overall development of a nation. Unemployment to TVET graduates in any country means either the country is on the wrong track of development or the TVET education not salable. Tracer study helps to move TVET in right track. Many TVET scholars emphasize conducting tracer study frequently to save TVET from quality erosion. Selection of a method and instrument, preparation for a survey, case study and focus group discussions are the major activities to be performed to conduct tracer studies. Here, an elaborate description is made on the entire process of Tracer Study conducted in the TVET. The views of graduates as well as their employers are the main data to pull out findings and refinement has to be done accordingly. Data collection should be more accurate and tools used should be appropriate for giving right direction to TVET. CTEVT and the central and administered Technical Institutions are conducting tracer studies from time to time to reflect reality. But, the application of the findings of tracer studies is a big question in CTEVT such as the revision of curriculum does not happen for a long time. As a result, the unemployment rate of graduates is on rise. Real tracer studies with commitment for change as per market need are the demand of modern TVET.